THE EXTENT TO WHICH PUBLIC RELATIONS STUDENTS HAVE SCIENTIFIC RESEARCH SKILLS AT YARMOUK UNIVERSITY - Dr. Farhan Olaimat (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims at acknowledging the extent to which public relations and students have scientific research skills at Yarmouk University and the challenges they confront as well as their suggestions to improve their scientific research skills concerning media research. The study adopted the descriptive approach that used field survey on sample of Public Relations and Media students at the Faculty of Mass Communication at Yarmouk University. It consisted of (300) bachelor students who study an Introduction to Media Research Course at the Faculty of Mass Communication. Also, field interviews with the group of teachers in the Department of Public Relations and Media were conducted with the group of teachers who teach such course from the same department at Yarmouk University